PERAN INOVASI PRODUK DALAM MEMEDIASI PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN UMKM KULINER DI BADUNG - Putriasih, Desak Made; Giantari, I Gusti Ayu Ketut (Buletin Studi Ekonomi; VOL.26.NO.2.AGUSTUS 2021DO - 10.24843/BSE.2021.v26.i02.p05, 2021)
In the current era of globalization, business development, especially in culinary MSMEs, is fast. To face competition requires the ability to innovate in products and improvement in marketing performance. The purpose of this study is to explain role of product innovation in mediating the influence of entrepreneurial orientation on marketing performance. This research was conducted in Badung Regency on the owners or managers of culinary MSMEs. The number of samples in this study were as many as 40 culinary MSMEs using purposive sampling method. Data collection was carried out by distributing questionnaires. The results show that entrepreneurial orientation had a positive but insignificant effect on marketing performance; Entrepreneurial orientation positively and significantly influences product innovation; Product innovation positively and significantly influences marketing performance and product innovation significantly mediates the effect of entrepreneurial orientation on marketing performance.